Answer :

Assume x = sinθ


= sin–1


= sin–1


= sin–1


= sin–1


sin(A+B) = sinAcosB+cosAsinB


The above expression can be written as


= sin–1


=


But θ = sin–1x


the above expression becomes sin–1x.


The given equation simplification to sin–1x.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers